(untitled) (The Review of Diabetic Studies, 2025)
Background: Diabetes mellitus is a long-term metabolic disease that requires ongoing medication and regular lab tests to keep blood sugar levels as low as possible.. Effective diabetes management is still hampered by poor medication adherence and poor laboratory result interpretation, especially in tertiary care hospitals where patients frequently have complex clinical profiles. By optimizing drug use and improving the clinical application of laboratory data, an integrated approach comprising laboratory scientists and clinical pharmacists may enhance therapeutic results. Aim: was to assess how an integrated approach comprising laboratory scientists and clinical pharmacists affected the glycemic control and medication adherence of diabetic patients who were admitted to a tertiary care hospital. Methods: A cross sectional study involved adult patients with type 2 diabetes mellitus who presented themselves in outpatient clinics of a tertiary care hospital. Patients were split into two groups: those getting standard care and those receiving combined clinical pharmacist-laboratory support. We gathered and examined information on antidiabetic treatment, medication adherence, clinical parameters, test results (fasting plasma glucose and HbA1c), and demographics. Findings: Compared to patients getting standard treatment, patients who got integrated care showed significantly greater medication adherence scores and improved glycemic control, as seen by lower mean HbA1c values. Structured pharmacist counseling, prompt laboratory reporting, and improved glucose marker interpretation were linked to better results. Conclusion: Better glycemic control and medication adherence among diabetes patients were linked to the combined participation of clinical pharmacists and laboratory scientists. In tertiary care facilities, putting multidisciplinary collaborative models into practice may improve patient outcomes and diabetes control.